1995
DOI: 10.1002/ar.1092420404
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain expression within the tapered ends of skeletal muscle fibers

Abstract: We postulate that longitudinal growth of myofibrils in adult muscle is characterized by the sequential expression of MyHC isoforms similar to that observed in rapidly growing muscle and that the presence of the neurotransmitter hydrolase AChE at the tapered fiber ends may be related to the retention of neonatal MyHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 71 publications
4
16
0
Order By: Relevance
“…The role of the tongue in mastication places it under compressive stresses not associated with appendicular muscle and places it at risk for accidental biting, and the low level of developmental MHC mRNA in the tongue body suggests that fiber regeneration is not routine. MHC-neo has been reported to be expressed in the tapered ends of fibers, particularly in birds [Rosser et al, 1995], and the low level of MHC-neo we found in tongue homogenates is consistent with expression restricted to very few fibers or fiber subdomains, such as tapered ends.…”
Section: Developmental and Unconventional Mhc Expressionsupporting
confidence: 87%
“…The role of the tongue in mastication places it under compressive stresses not associated with appendicular muscle and places it at risk for accidental biting, and the low level of developmental MHC mRNA in the tongue body suggests that fiber regeneration is not routine. MHC-neo has been reported to be expressed in the tapered ends of fibers, particularly in birds [Rosser et al, 1995], and the low level of MHC-neo we found in tongue homogenates is consistent with expression restricted to very few fibers or fiber subdomains, such as tapered ends.…”
Section: Developmental and Unconventional Mhc Expressionsupporting
confidence: 87%
“…A study of transverse and longitudinal sections showed that the small fibre which expressed IGF-1 mRNA also express the neonatal myosin heavy chain (MyHC). It has also been shown that small diameter fibres containing neonatal MyHC are the tapered ends of the larger fibres terminating within the belly of the muscle (Rosser et al, 1995). Longitudinal growth of skeletal muscle is facilitated by the addition of new sarco- meres to the ends of the existing myofibrils (Williams & Goldspink, 1971, 1973 and the initial stage involves the laying down of neonatal myosin (Rosser et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This work showed that IGF-1 gene expression is not confined to the satellite cells but is up-regulated in the muscle fibres themselves. In transverse sections the IGF-1 message was localized to large muscle fibre but tended to be expressed strongly in the small fibres which represent the tapered ends of fibres terminating in the muscle belly (Rosser et al, 1995). In a few muscles some evidence of degeneration and regeneration was noted with high IGF-1 mRNA levels.…”
Section: Localization Of Igf-1 Mrna In Normal and Stretched Musclementioning
confidence: 94%
“…In maturing rat SOL muscles, regional asymmetries in fiber type are present in single fibers between 3 and 4 weeks of age, but these fibers then become more homogeneous over time [Sakuma et al, 1995]. In developing bird muscles, neonatal MHC is expressed at the growing ends of the fibers, but adult MHCs are found at the muscle mid-regions [Rosser et al, 1995]. We found that in many cases, one end of the fiber differed in MHC content as compared with the rest of the fiber ( fig.…”
Section: Segmental Differences In Fiber Typementioning
confidence: 99%